El comic como estrategia didáctica para desarrollar la competencia escribe diversos tipos de textos narrativos - Sanchez Alvarado, Bladimiro (2021)
The present work of professional sufficiency entitled: "The comic as a didactic strategy to develop competence writes various types of narrative texts in elementary school students." Its objective is to determine the influence of comics as a didactic strategy to develop the competence of writing various types of written (narrative) texts in their mother tongue. We worked with a population of 170 students and a sample of 22 students in the fourth grade of primary education. The production of narrative texts through the comic requires an ability to organize information, communicative purpose, creativity, originality to achieve the performance of the communication area. For this reason, the aim is for students to learn to communicate their experiences, anecdotes inside and outside of school. The learning session was put to the test through a text production card that verified the necessary criteria to specify the writing of the comic.